Monitoring physicochemical parameters in the bioremediation of soil contaminated by petroleum hydrocarbons using poultry manure - Guimarães, C. C.; Guireli Netto, L. [UNESP]; Barbosa, A. M. (Springer Nature, 2024)
Soil contamination and its impact on human health are growing concerns worldwide due to anthropogenic activities, as soil plays a central role in the absorption of pollutants, including petroleum hydrocarbons. Conventional soil remediation techniques can have significant environmental impacts. Sustainable approaches are therefore needed, and bioremediation has emerged as a promising alternative. The addition of poultry manure, which is rich in nutrients and microorganisms, is a valuable resource for enhancing bioremediation processes. In this study, we investigated the use of stabilized and composted poultry manure in different proportions for the remediation of a tropical soil artificially contaminated with diesel oil. The results showed that both compost and stabilized manure treatments significantly reduced hydrocarbon concentrations in 60 days, with degradation rates ranging from 2.00 (w/w) to 6.96% (w/w) per day. Differences between treatments were observed in the improvement of soil structure and moisture retention. Treatments with lower percentages of compost and manure were the most effective, suggesting their suitability for the remediation of hydrocarbon-contaminated soils. In conclusion, the use of poultry manure as an organic amendment for soil remediation is a sustainable and efficient approach, especially for soils with low organic matter and reduced microbial populations. This research contributes to the development of effective remediation strategies in regions with a history of intensive industrialization and contaminated areas, ultimately promoting environmental sustainability and human health.
Keywords: Environmental contamination; Remediation; Sustainable environmental remediation; Total petroleum hydrocarbons